Environmental regulations, financial constraints and export green-sophistication: Evidence from China's enterprises. (1st April 2020) - Ge, Tao; Li, Jinye; Sha, Ru; Hao, XiongLei
Abstract: Environmental governance and financial difficulties are crucial factors affecting the green technology intensity of enterprises' exports. This paper investigates the heterogeneous effects of environmental regulations (ER) and financial constraints (FC) on export greensophistication (EGS) in China. Using an enterprise-level panel dataset for the period 1998–2007, the empirical results show that both ER and FC have positive and negative effects, respectively. However, the positive effect of ER does not fully offset the negative effect of FC, and the net effect of the two causes the actual level to deviate negatively from the effective level. Further grouping tests indicate that the actual level is still below the effective level, but the negative net effect of enterprises is different, among which publicly-held enterprises and mildly-polluting enterprises are the most significant in their respective groups. The EGS does not reach the international level, which is an important reason for China's export to be "large but not strong". According to the change of the net effect, although the improvement of China's EGS is a long-term and arduous, China is expected to become astrong trading country. Highlights: Environmental regulations promote green technology intensity of China's exports. Financial constraints inhibit green technology intensity of manufacturing industry. The promotion is below the inhibition, making exports with low green-sophistication. Enterprises differ in product quality, but generally do not reach an effective level. China is expected to increase competitive advantage by transforming trade patterns.